PENGEMBANGAN USAHA KELOMPOK PERAJIN TEMPE DI KECAMATAN CANDI KABUPATEN SIDOARJO - REKAPANGAN, Jariyah, Tri Mulyani S,Sudaryati HP , Su (UPN VETERAN JAWA TIMUR, 2014)
ABSTRACT Â There are 500 artisans of tempeh inÂ Sepande village, subdistrict Sidoarjo, but it was not incorporated as a member of the Primary Cooperative Producers of Tofu- Tempeh Indonesia (PRIMKOPTI)